PENGARUH KOMBINASI ANKLE PUMP EXERCISE DAN ELEVASI KAKI 30° TERHADAP EDEMA KAKI PADA PASIEN CKD - Mohammad Arifin Noor; Wulan Maulia Riska; Suyanto Suyanto; Indah Sri Wahyuningsih (SEKOLAH TINGGI ILMU KESEHATAN KESDAM IV DIPONEGORO, 2023)
Introduction: Chronic Kidney Disease (CKD) is a condition in which the kidneys have experienced functional or structural damage or disturbances. The condition of the kidney that has decreased function is unable to dispose of waste products through urination which can result in disruption of endocrine, fluid, electrolyte, metabolic and acid-base functions, one of the consequences of which is the occurrence of edema. The prevalence of kidney failure in Central Java reached 0.42% with a total of 96,794 sufferers. The impact of edema that is not treated will result in respiratory, cardiovascular systems, neurological systems. The purpose of this study was to see the effect of a combination of ankle pump exercise and 30° foot elevation on edema in CKD patients at the Sultan Agung Islamic Hospital in Semarang. Method: This research is a quantitative study using a pre-experimental pretest-posttest design approach. The sample is 12 respondents with purposive sampling technique. Results: The results of this study were mostly male with a total of 10 with a percentage of 83.3% with an average age of 44.50. the results of the bivariate analysis with the Marginal Homogeneity Test obtained a significant value of p = 0.001 (<0.05). Conclusion: There is an effect of a combination of ankle pump exercise and 30° foot elevation on foot edema in CKD patients.